The Effect of Sales Promotion on Purchase Intention and Purchase Decision of Telkomsel Data Packages in Morowali Regency: The Effect of Sales Promotion on Purchase Intention and Purchase Decision of Telkomsel Data Packages in Morowali Regency - Rahma Wati; Moh Zeylo Auriza; Maskuri Sutomo; Muhammad Isra Iradat (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2026)
This study is motivated by inconsistent empirical findings related to the influence of sales promotion on purchase decision, especially in utilitarian products that are basic needs, such as data packages. In needs-based products, consumers generally make purchases due to functional impulses, so the effectiveness of sales promotions in influencing purchase decision directly or through purchase intention still needs to be studied, especially in the context of regional markets. The study examines the influence of sales promotion on purchase decision through purchase intention in Telkomsel data package users in Morowali Regency. This study uses purposive sampling as a sampling technique, where the researcher determines the sample based on the research objectives and criteria that have been set by the researcher. The quantitative approach was used with SmartPLS-based Structural Equation Modeling (SEM) analysis techniques on 140 respondents. The results of the analysis show that sales promotions are proven to have a direct effect on purchase intention, but do not show an effect on purchase decision. On the other hand, purchase intention has a direct effect on purchase decision and has been proven to mediate the relationship between sales promotion and purchase decision indirectly. The novelty of this study lies in proving that in utilitarian products in the Morowali Regency market, sales promotion plays a role as a psychological trigger for the formation of purchase intention rather than as a driver of direct purchase decision. These findings strengthen the role of purchase intention as a mediation mechanism for needs-based products